Study of diathesis. - Fairweather, D. Stanley (The University of Edinburgh, 1941)
The study, then, has brought the writer to the following conclusions: -

1). Disease has significance for the patient, greater than the study of its pathology has for the physician.

2). Such significance resides in the past history, but has also something to say about the future.

3). Psychiatric modes of examination will be of increasing value to those who are interested in the relation of effect to cause.

4). Our present increase of knowledge of hormones is providing us with the link between physiology and pathology.

5). Treatment in the future is going to be much more a concern for the psychiatrically trained than appears at present.

6). A more dynamic approach to illness is emerging, in which our attention will be devoted more to the evolution of health and sanity, than with the static preoccupation with a diseased person.

7). This will involve, therefore, a concern for the following desiderata :- a). Psychiatric History. b). Growth History. c). Developmental indicators. d). Family History. e). Clinical History. f). Clinical examination. g). The attempted orientation of nature and nurture to endocrine factors. h). A definite policy of follow -up over some years. i). An attempt at evaluation of the illness in terms of the personality of the patient. j). The successful application by psychotherapy to meet the patient's need, both as a social unit and as an individual. k). As far as chronic ill -health is concerned, at any rate, an attempt to reduce drug treatment to a minimum, and to foster in the patient more self-reliance.

The present work began as a clinical and anthropometric study based largely on actual observations made during the years 1928-1932, but as the full significance of those facts has not yet made itself apparent, the writer has omitted any detailed reference to them in order that the more general and philosophical aspects, which have assumed for the present greater preoccupation, might be elaborated.